Concepções de sustentabilidade e sua relação com as vertentes de educação ambiental: um estudo da UFSCar campus Sorocaba - Oliveira, Clarissa Suelen (Universidade Federal de São Carlos, 2019)
Environmental education goes through multiple interpretations. Layrargues and Lima propose three political-pedagogical macro trends of environmental education: conservationist, pragmatic and critical. In the critical cnception of environmental education, the component of Critical-transforming Environmental Education brings an environmental education conception based on Freire’s pedagogy through the generative themes, based on the problematization and comprehension of social contradictions lived in the current socioeconomical system aiming at the transformation of reality, and based on the emancipation and humanization of the subjects. Among the principles of environmental education is sustainability, whose conception around it is polysemic. The fact that UFSCar – Sorocaba Campus adopted such principle in the context of its creation has turned it into an example for this research. Thus, the main objective of this work is to explicit the implications of the different conceptions of sustainability for the strands of environmental education, in its relation to UFSCar – Sorocaba Campus. For that, we did a literature review on sustainability, bringing its implications for environmental education and adopting the macro trends of Layrargues and Lima’s environmental education as analytical parameters. In the context of UFSCar – Sorocaba Campus we analyzed: 1) the documented and undocumented trajectory of the events, through the analysis of three main documents about the institution; 2) the application of a questionnaire to the teachers who were part of the construction and creation of the campus; 3) transcripts of semi-structured interviews conducted with teachers and managers who participated in the creation of the Sorocaba Campus. Procedures of discursive textual analysis were used to the analysis of these data. The results obtained allowed to relate book authors conceptions of sustainability as conservative and critical, and allowed to establish relations with macro trends of environmental education. Thus, conservative conceptions of sustainability may be related to Conservationist and Pragmatic environmental education macro trends, and critical concepts may be related to Critical environmental education macro trends. In the context of UFSCar - Sorocaba Campus, it was possible to understand that the principle of sustainability adopted when the campus was created can be classified as conservative, whose environmental education conceptions appear pragmatic. The analysed documents, sometimes, bring a Critical environmental education speech. In order to implement this (Critical) environmental education concept in the institution, we highlight the contributions of the Critical-transforming Environmental Education: the component the role in the formation of multiplying agents in favor of social transformation, the overcoming of contradictions from the current socioeconomic system and the emancipation of subjects to a more just and egalitarian world.
Sustainability concepts and its relation with environmental education: an UFSCar campus Sorocaba study
Concepciones de sostenibilidad y su relación con las vertientes de educación ambiental: un estudio de la UFSCar campus Sorocaba
Keywords: Macrotendências de educação ambiental; Concepções de sustentabilidade; Universidade; Formação de educadores; Educação Ambiental Crítico-transformadora; Macro trends of environmental education; Conceptions of sustainability; University; Training of educators; Critical-transforming Environmental Education; Macrogendencias de educación ambiental; Concepciones de sostenibilidad; Universidad; Formación de educadores; Educación Ambiental Crítico-transformadora; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO